2011
DOI: 10.1177/0743558411409931
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Mental Illness Stigma Among Youth in Psychiatric Outpatient Treatment

Abstract: This research explores the experiences of mental illness stigma in 24 youth (58.3% male, 13-24 years, 75% Latino) in psychiatric outpatient treatment. Using Link and Phelan’s (2001) model of stigmatization, we conducted thematic analysis of the interview texts, examining experiences of stigma at individual and structural levels, in addition to the youths’ social-psychological processes. Youth in psychiatric treatment acknowledged that their larger cultural context holds pejorative viewpoints toward those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 40 publications
(77 reference statements)
1
95
1
3
Order By: Relevance
“…Limited experiences of stigma may also be a function of the youth's age as their constricted social experiences may have restricted opportunities for stigma experiences. 24 Alternatively, this younger generation, living in the United States may experience less HIV/AIDS-related stigma as they and their peers have not seen the wasting and imminent death that was experienced early in the epidemic or in countries with limited access to treatment. It is also possible that youth in this study were too young to understand/conceptualize HIV-related stigma.…”
Section: Disclosure Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited experiences of stigma may also be a function of the youth's age as their constricted social experiences may have restricted opportunities for stigma experiences. 24 Alternatively, this younger generation, living in the United States may experience less HIV/AIDS-related stigma as they and their peers have not seen the wasting and imminent death that was experienced early in the epidemic or in countries with limited access to treatment. It is also possible that youth in this study were too young to understand/conceptualize HIV-related stigma.…”
Section: Disclosure Statusmentioning
confidence: 99%
“…23 Similar to youth with other stigmatized illness (e.g., epilepsy, psychiatric disorders), youth whose HIV status becomes public may experience or perceive discrimination and rejection from others, and subsequently withdraw. [24][25][26] Even youth who have not told others about their HIV status may experience internalized stigma in the form of shame, self-blame, and stress related to hiding a potentially damaging ''secret'' from others as they engage with the negative evaluations of what it means to be HIVþ found within their immediate and broader social context. 27 Although numerous studies have explored stigma experiences among adults living with HIV, [20][21][22] stigma experiences of PHIVþ youth are not well understood.…”
mentioning
confidence: 99%
“…According to Gonzales and colleagues (3), a greater readiness to engage in treatment will improve short-term adherence, and adherence is improved when the patient understands the potential benefits of treatment. However, a young person with mental illness may experience individual discrimination or rejection in their social environment (46). It has been found that increases and decreases in depressed symptoms immediately after treatment changes are related to patient expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of these tasks may be compounded for youth receiving psychiatric treatment who have been “labeled” as mentally ill and who are particularly susceptible to the negative evaluation from peers or others in their environment (Elkington et al, 2012; Moses, 2010a, 2010b). The effects of MI stigma may have considerable ramifications for an individual’s developing identity (Rappaport & Chubinsky, 2000), and may impose challenges to developing a healthy self-concept, engaging in romantic and intimate relationships, and practicing safer sex behaviors.…”
mentioning
confidence: 99%